ORFIL: Cocopeat–Rice Straw Air Filter for Reducing Motorcycle Exhaust Emissions - Muhamad Naufal Muzhaffar; Dafa Arkananta Saputro; Alawi Hadad El Shirazy; M. Rizkie Akbar Gumilar; Kenzie Abiyyu Pranaja; Agung Taufik (Journal Educational Research and Development | E-ISSN : 3063-9158, 2026)
The increasing number of motorcycles in Indonesia contributes to air pollution, including exposure to particulate matter and ultrafine particles that may affect human health (Schraufnagel, 2020; Masruroh, 2015). This study developed and evaluated ORFIL, a natural air filter made from cocopeat (coconut husk waste) and rice straw, to reduce motorcycle exhaust emissions. The filter material was prepared by dehydrating 70 g cocopeat and 70 g straw for 48 hours, grinding each into coarse powder, mixing them, and packing the mixture inside a factory filter frame using tulle fabric as a retaining layer. Emission performance was tested on one motorcycle (motorcycle X) by comparing the factory-installed foam filter and ORFIL using measured exhaust parameters (CO, HC, CO₂, and O₂). The ORFIL filter produced lower emissions than the factory filter: CO decreased from 0.04% to 0.027%, HC decreased from 19 ppm to 15 ppm, and CO₂ decreased from 0.6% to 0.48%, while O₂ increased from 20.41% to 22.2%. These results indicate that cocopeat and rice straw have practical potential as low-cost natural filter media, consistent with prior findings on coconut fiber and straw-based filtering materials (Lay & Pasang, 2003; Wahyuningrum et al., 2014; Surjosatyo, 2020).